Incorporation of Telehealth Into Multidisciplinary Clinics: Visits Via Video Offer Advantages for Team and Families. Issue 4 (4th April 2022) - Gleghorn, Elizabeth E.; Hilk, Susan S.; Rothbaum, Robert
Abstract : ABSTRACT: Shelter in place orders in the coronavirus disease 2019 (COVID-19) pandemic necessitate changes in how medical care is delivered. We describe our method for team telemedicine visits for California Children's Services, a state insurance for children requiring multidisciplinary care, to demonstrate how such visits can be efficiently conducted. Although the physical distance provides some obstacles, telemedicine visits can also improve some elements of the team visit.